Expression Pattern of Ngb in Astrocytes after Spinal Cord Injury and the Clinical Significance - Liu, Zengqiang; Song, Bo (Cellular and Molecular Biology, 2022)
In the current study, we evaluated the expression pattern of neuroglobin (Ngb) in the astrocytes after spinal cord injury (SCI) and explore the clinical significance. For this purpose, a total of 48 Sprague-Dawley rats were divided into the SCI group (n = 40) and Sham group (n = 8). Rats in the SCI group were used to prepare the SCI models by using the modified Allen’s method, followed by the HE staining to observe the post-SCI pathological changes and immunofluorescent staining to observe the dynamic changes of Ngb in astrocytes after SCI. Then, oxidative stress injury models were constructed on the astrocytes in the spinal cord of rats by using peroxide in different concentrations (0, 50, 100, 150, 200 and 400μmol/L), and at 6 and 12 h after treatment, the vitality of astrocytes that were treated by peroxide in different concentrations was determined using the MTT method, while the ability of astrocytes to generate radical oxygen species (ROS) was determined by using the flow cytometry. The mRNA expression of Ngb after the oxidative stress injury in astrocytes was measured by using the real-time quantitative PCR. Results of HE staining demonstrated that rats with SCI presented with the gradual transition from acute injury into the glial scar, a natural repair, while the results of immunofluorescent staining indicated that after SCI, expression of Ngb in the astrocytes experienced an increase followed by a decrease, and the peak level was attained at 14 d after SCI. Following the treatment of H2O2 at different concentrations (50, 100, 150, 200 and 400μmol/L) for 6 and 12 h, the vitality of astrocytes in the model groups was significantly lower than that in the control groups (all P < 0.05). As the concentration of H2O2 increased (50, 100, 150, 200, 400μmol/L) and exposure to H2O2 prolonged (6, 12 h), mRNA expression was firstly increased but then decreased in astrocytes in a time-dose dependent pattern (all P < 0.05). After SCI, the expression of Ngb in the astrocytes of spine was upregulated, suggesting that Ngb may be involved in the anti-oxidative stress injury in astrocytes after SCI, thereby playing as an endogenous protector of cells.